Análise da superfície de fratura do aço inoxidável duplex UNS S31803 através da aplicação da geometria dos fractais - Silva, Eloy de Macedo (2002)
In the last years, the fractal geometry has become widely studied. Its application in several areas increased substantially, particularly in materials engineering and science, aiming the analysis of failures and the study of the mechanical properties of materials. Some studies have shown the relationship between the fracture surfaces and their mechanical properties using the fractal geometry and its properties of fractal dimension and selfsimilarity. In this research, the fracture surface of duplex stainless steel, which was obtained by the Charpy impact test, was studied applying the fractal geometry. Considering the 475°C embrittlement, the steel was submitted to thermal aging to obtain the fracture surfaces, whose images were captured by the scanning electron microscope (SEM). In the fractal analysis, a study was made applying the island method and profile analysis through the digitalization of the images and the application of image analyzing software. Emphasis was given on the calculation of the fractal dimension (FD) of the surface, on the energy absorbed during the impact test, on the involved fracture mechanisms and as well on the relationship between FD and thermal aging. In order to better understanding the subject, it was done the review about fracture mechanics, of duplex stainless steel and of fractal geometry. Finishing the research, the obtained fracture surface, the absorbed energy and the obtained values of FD were analyzed. The obtained results demonstrated a relationship between the fractal dimension, the size of the dimples in fracture surfaces and the impact energy to obtain them.